Amine-functionalized bimetallic Co/Zn-zeolitic imidazolate frameworks as an efficient catalyst for the CO2 cycloaddition to epoxides under mild conditions. (July 2022) - Nguyen, Que Thi; Do, Xuan Huy; Cho, Kie Yong; Lee, Yu-Ri; Baek, Kyung-Youl
Abstract: Amine-functionalized bimetallic zeolitic imidazolate framework-8 (Co/Zn-ZIF-A) with 3-amino-1, 2, 4-triazole (Atz) was synthesized by a post-synthetic modification and utilized as a heterogeneous catalyst for the synthesis of cyclic carbonates from CO2 and epoxides. Different amine contents in Co/Zn-ZIF-A materials were controlled by adjusting the ligand exchange reaction time of the of 2-mIM with Atz. Co/Zn-ZIF-A-24 h with the highest amine contents (32% of Atz) achieved an excellent result of 99% conversion of epichlorohydrin with high selectivity of > 99% after 24 h without co-catalyst and solvent under mild conditions (80  o C, 1 bar CO2 ). The enhanced catalytic activity is attributed to the acid-base synergistic effect by the combination of bimetallic systems consisting of Zn and Co as Lewis acid sites and the abundant Lewis bases sites of -NH2, -NH groups from Atz ligand. A kinetic study of the cycloaddition reaction over Co/Zn-ZIF-A-24 h confirmed an approximately first-order dependence on the epichlorohydrin concentration and CO2 pressure with an activation energy of approximately 39.5 kJ mol -1 . Co/Zn-ZIF-A-24 h catalyst showed good reusability with no obvious loss in catalytic activity during five recycling runs and its structural stability was also confirmed. A plausible reaction mechanism of Co/Zn-ZIF-A catalyst for CO2 -epoxide cycloaddition was proposed. Graphical Abstract: Amine-functionalized bimetallic Co/Zn-ZIF-A exhibits excellent catalytic activity for CO2 cycloaddition to epoxides without solvent and co-catalyst under mild conditions. ga1 Highlights: Amine-functionalized bimetallic Co/Zn-ZIFs (Co/Zn-ZIF-A) were synthesized by post-synthetic modification. Co/Zn-ZIF-A was found to be catalytically efficient for CO2 /epoxide coupling reaction under mild conditions. Synergistic effect of amine groups and bimetallic systems on accelerating the epoxide ring-opening. Co/Zn-ZIF-A demonstrates excellent catalytic activity without solvent and any co-catalyst.